North Korea's political economy: Hybrid economic institutions and the contributions of German order policy (Ordnungspolitik) - Bernhard Seliger (OrdnungsPolitisches Portal (OPO), 2020)
The dominant debate about the nuclear crisis often clouded the view of Western and South Korean observers regarding the deep changes, North Korea's political and economic system underwent in the Kim Jong-Un era, from the Soviet socialist system under his grandfather Kim Il-Sung and the military dominance under his father Kim Jong-Il. The ideological development from the "military first" doctrine to "byungjin line" (parallel development of economy and nuclear power) to the current "economy first" doctrine made new governance mechanisms necessary. In particular, the larger role of markets and the larger role of market mechanisms in economic policy needed new institutions, which are, however, often lacking. Instead, hybridization of economic institutions spontaneously emerges, leading sometimes to improved economic performance, but hindering the full effect of market reforms. One example are the new special economic zones lacking coordination; even apart from strangling sanctions they are all without success to date. One important question is, how stable hybrid institutions can be. Will they lead to a more "pure" (market type) economic system, as Eucken predicted, or will they create a new form of mixed economy with North Korean characteristics? Also, the core question of the impact on markets on political stability has to be answered.
Keywords: 330; North Korea; Economic Policy; Economic order; institutional development